Antitrust Damage Claims: A View From Efta Court - Agata Jurkowska-Gomułka (Market and Competition Law Review)
Articles 101 and 102 TFEU have become a pattern for competition rules provided in Articles 53 and 54 of the EEA Agreement, which entered into force on 1 January 1994. Both EU competition law and EEA competition law can be enforced before national courts. Lodging damage claims in the EU was facilitated by Directive 2014/104/EU. The so-called Antitrust Damages Directive was highly inspired by the jurisprudence of the Court of Justice of the European Union. Although Directive 2014/104/EU has not been incorporated into the EEA law, damage claims resulting from violations of EEA competition rules are judged by national courts in the EEA Member States, which is why some aspects of private enforcement of competition law have become a point of interest for the EFTA Court, being – together with the Court of Justice of the European Union – the EEA court. Firstly, the article aims at checking if the EFTA Court jurisprudence on antitrust damage claims follows the guidelines formulated in the case law of the Court of Justice. Since the positive answer to this question is highly probable, secondly, the article aims at identifying the extent of the impact of EU jurisprudence in private enforcement cases on judgments of the EFTA Court. The article concludes that the EFTA Court’s activities regarding antitrust damage claims follow the route indicated by the Court of Justice of the European Union. Four identified judgments regarding – directly or indirectly – antitrust damage claims (Nye Kystlink, Fjarskipti, Schenker I and Schenker V), delivered by the EFTA Court, seem to strengthen its position as an institution that is able to guarantee a coherence between EEA and EU competition law. EFTA Court’s judgments in private enforcement cases are also a point of interest and reference for EU Advocates General and can become an inspiration for both EU and national case law.